WORKING FEATURES OF POWER SOURCE SYSTEMS – A MULTIPLE CURRENT PULSE GENERATOR - Argun, Schasyana V. (National Technical University "Kharkiv Polytechnic Institute" and Аnatolii Pidhornyi Institute of Power Machines and Systems of NAS of Ukraine, 2013)
An analysis of circuit designs as to connecting a magnetic pulse action tool to a power source has been carried out. Design features of a magnetic pulse installation control and monitoring system in a multiple current pulse mode have been revealed. The description of the control and monitoring system block diagrams has been presented.